Increased cerebellar volume and BDNF level following quadrato motor training. Issue 1 (20th October 2014) - Ben‐Soussan, Tal Dotan; Piervincenzi, Claudia; Venditti, Sabrina; Verdone, Loredana; Caserta, Micaela; Carducci, Filippo
<x xml:space="preserve">Abstract</x> Using whole‐brain structural measures coupled to analysis of salivary brain‐derived neurotrophic factor (BDNF), we demonstrate sensory motor training‐induced plasticity, including cerebellar gray matter volume increment and increased BDNF level. The increase of cerebellar volume was positively correlated with the increase of BDNF level. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>